PENGATURAN SUHU DALAM RUANGAN SECARA DIGITAL - Huda, Sakti Nur (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2009)
Digital system used in equipments electronica, inclusive of among other things used as a means ofcontroller or arrangement. In this case to fulfill requirement of temperature condition of the desired, humanbeing a lot of designing a appliance which can be used to arrange temperature. For that this final projecttake problems how planning and make a appliance of temperature arrangement with digital system.instrument Used in this research consisted by network of temperature changer to tension(tranduser), analogous network of digital to converter ( A/D Converter), BCD seven Segment, and theappearance, network of controller and appliance of temperature changer and also power supply asgenerating tension for each of the network.Principle work this appliance is tranduser used in this network will yield tension, what resulted froma accepted by temperature change of the tranduser. output tension Yielded from tranduser exploited asinput of analogous changer network to digital, then the yielded output, in the form of digital code by networkof decoder BCD to seven segment, presented a displayed (seven segment). Tension Output from tranduserexploited as input tension for the controller network.Keyword : tranduser, ADC (analog to digital converter), BCD (binary code decimal), seven segment